Preoperative and predischarge predictors for persistent pulmonary hypertension after mitral valve surgery in patients with chronic organic mitral regurgitation - Rina Ariani; Indriwanto Sakidjan; Budhi Setianto (Jurnal Kardiologi Indonesia, 2014)
Objectives. This study sought to evaluate the prevalence of pulmonary hypertension after mitral valve surgery ini patients with chronic organic mitral regurgitation and to determine preoperative and predischarge predictors for persistent pulmonary hypertension after surgeryMethods. This is a cohort retrospective study involving subjects with chronic organic mitral regurgitation with preoperative systolic PA pressure > 50 mmHg undergoing surgery. Demographic and echocardiography datas were collected prior to surgery, predischarge, and follow up datas were evaluated after minimal 6 months duration. Subjects were then devided into groups based on existence of persistent pulmonary hypertension after follow up. Bivariate and multivariate analysis was done to determine contributing factors.Results.There were 92 subjects with dominant mitral regurgitation included in this study with median age 40 (range 17-68) years with slight female predominance (55%). Persistent pulmonary hypertension was observed in 23 subjects (25%) predischarge and in 20 subjects (20.7%) after mean follow up of 11 + 5.5 months. Bivariate analysis revealed preoperative TAPSE, underlying etiology, severity of pulmonary hypertension preoperatively, postoperative atrial fibrilation, mean mitral valve gradient predischarge, and the presence of residual pulmonary hypertension predischarge were related with persistent pulmonary hypertension. From multivariate analysis, post operative atrial fibrillation [OR 7.3 (CI 95% 1.64-33.33, p=0.09)], mean mitral valve gradient predischarge [OR 1.67 (CI 95% 1,3-2.7, p=0.038)], and preoperative TAPSE [OR 0.143 (CI 95% 0.03-0.70, p=0.017)] were independent predictors for persistent pulmonary hypertension after mitral valve surgery.Conclusion. Persistent pulmonary hypertension was observed in 20.7% subjects after mitral valve surgery. Preoperative TAPSE, post operative atrial fibrillation, and predischarge mean mitral valve gradient were independent predictors.